Problematika Deteksi Tumbuh Kembang Anak Di Lembaga RA Wilayah Kedung - Quthrotunnada, Nikmah (JIEEC (Journal of Islamic Education for Early Childhood), 2024)
Early detection of child growth and development is an activity carried out to find deviations in growth and development in pre-school child The purpose of this study is to find out e sumn and explain the problems of data detection of child growth and devel@ment. The research method uses qualitative methods, namely by collecting data using observation, interviews, and documentation, data arsis using technical triangulation and source triangulation. The results of the research on child growth and development detection data obtained at the RA institution in the Kedung area have been fulfilled, but the data recap is not adjusted for the age of the child. As for the problems in the RA institution, the results of the data recap are adjusted based on class groups that are not suitable based on the age of the child Keywords: detection of growth and development, SDIDTK, development